Relations among perceived justice, work engagement, organizational commitment and turnover intention of medical workers - Yang Tiecheng (2021)
Taking hospitals at different levels in Shenzhen city as the research object, this thesis explored the influencing factors related to Perceived Justice, Work Engagement, Organizational Commitment and Turnover Intention of medical workers as well as their relations through literature review, questionnaire, Structural Equation Modeling (SEM) and statistical analysis, so as to provide scientific reference for hospital managers to optimize corresponding policies. Based on literature review and data analysis, this research forms seven hypotheses revolving around Perceived Justice, Work Engagement, Organizational Commitment and Turnover Intention. Except the hypothesis that Perceived Justice indirectly affects Turnover Intention through Work Engagement, the other hypotheses are all valid. The results showed that, there are positive correlations between Perceived Justice and Organizational Commitment, and between Perceived Justice and Work Engagement; there are negative correlations between Perceived Justice and Turnover Intention, Organizational Commitment and Turnover Intention, and between Work Engagement and Turnover Intention; and Organizational Commitment plays a mediating role in the negative correlation between Perceived Justice and Turnover Intention. On account of the study result, this thesis provided countermeasures and suggestions for hospital managers: Establish a scientific and reasonable performance-based compensation system to increase the Perceived Justice among medical workers; improve the career planning of medical workers and stabilize the talent team of hospitals; implement flexible management and provide more humanistic care to improve medical workers’ sense of belonging; create a corporate culture that encourages employees’ participation and thus enhance their sense of ownership; establishing an analytical system of turnover control to build an effective talent retention strategy.